THE ROLE OF A FASALITATOR TEACHER IN THE FORMATION OF ECO-AESTHETIC COMPETENCE AT A SMALL SCHOOL AGE - Alijonova Maftunaxon Maxamadjon Qizi (Scholars Digest Publishing, 2023)
The article covers who is the facilitator teacher and what characteristics it should have, the peculiarities of sigmenting eco-aesthetic competence in students of a small school age, the tasks and burdens that the teacher should perform in this regard, and the role and role of maturing eco-aesthetic competence in the person of the student in the life of society is high.
Keywords: facilitator teacher, trend, competence, facilitator, farm, group dynamics, environmental situation.